2016
DOI: 10.1142/s021798491650072x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Y2O3insertion layer on anisotropic magnetoresistance of Ni81Fe19 films

Abstract: A series of Ta(4 nm)/Y2O[Formula: see text]/Ni[Formula: see text]Fe[Formula: see text](20 nm)/Y2O[Formula: see text]/Ta(3 nm) films were prepared on glass substrates by magnetron sputtering under appropriate conditions. AMR value, phase composition and magnetic hysteresis hoop of Ni[Formula: see text]Fe[Formula: see text] films were measured and analyzed by four-point probe technology, X-ray diffraction (XRD) and vibrating sample magnetometer (VSM), respectively. Influence of Y2O3 which work as oxidation inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…As t Hf increases from 0 to 1 nm, the AMR ratio increases from 3.8 to 4.8%. The maximum AMR ratio is much higher than that reported in other literature studies, as shown in Figure i. Actually, a similar AMR enhancement effect with Hf insertion is observed for other annealing conditions (Figure S2), indicating good reproducibility of the effect.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…As t Hf increases from 0 to 1 nm, the AMR ratio increases from 3.8 to 4.8%. The maximum AMR ratio is much higher than that reported in other literature studies, as shown in Figure i. Actually, a similar AMR enhancement effect with Hf insertion is observed for other annealing conditions (Figure S2), indicating good reproducibility of the effect.…”
Section: Resultssupporting
confidence: 76%
“…The inset shows the magnetoresistance curves of films before and after inserting 1 nm Hf. (i) Comparison of the AMR ratio between our designed structure and other reported structures in literature studies. …”
Section: Resultsmentioning
confidence: 99%